MEASURING CONSUMER LOYALTY THROUGH SERVICE QUALITY AND CUSTOMER SATISFACTION IN WORKSHOP DIAN SERVICE PEMATANG SIANTAR - Sisca, Sisca; Wijaya, Andy; Widianti, Retno (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Consumer loyalty is very important for businesses and organizations because loyal consumers will generally show attitudes and behavior that are profitable for a particular business.The purpose of this research was to determine the effect of service quality and consumer satisfaction on consumer loyalty at Bengkel Dian Service Pematang Siantar both simultaneously or partially.This research uses library research and field research design. The sample of this research is consumers of Bengkel Dian Service Pematang Siantar, which is 53 people.The results of this research can be concluded as follows: 1. Service quality is good, consumer satisfaction is satisfied and consumer loyalty is high. 2. There is positive effect between service quality and consumer satisfaction on consumer loyalty. 3. There is high correlation between service quality and consumer satisfaction with consumer loyalty. H0 is rejected, meaning that service quality and consumer satisfaction have positive and significant effect on consumer loyalty at Bengkel Dian Service Pematang Siantar both simultaneously or partially.